Postoperative Health-Related Quality of Life of Cervical Cancer Patients – A Comparison between the Wertheim-Meigs Operation and Total Mesometrial Resection (TMMR) - Sowa, E.; Kuhnt, S.; Hinz, A.; Schröder, C.; Deutsch, T.; Geue, K. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: The present study compares for the first time the standard therapy for cervical cancer in FIGO-stages IB-IIB, radical hysterectomy according to the Wertheim-Meigs operation, with the newly developed, nerve-sparing surgical technique, total mesometrial resection (TMMR) with regard to postoperative, health-related quality of life. Method: In the framework of a multicentre, retrospective cohort study a total of 110 cervical cancer patients were interviewed once by means of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and the cervical cancer module (EORTC QLQ-CX24). The influence of the surgical method was investigated by analysis of covariance under control of age and the time elapsed between treatment and interview. Results: An influence of the therapeutic method was demonstrated in the EORTC scales physical function (p = 0.047), role function (p = 0.016), fatigue (p = 0.028), pain (p = 0.018), shortness of breath (p = 0.034), lack of appetite (p = 0.006) and diarrhoea (p = 0.012) in favour of the 74 women treated by TMMR. With regard to cognitive, emotional and social functioning as well as cervical cancer-specific symptoms, no significant differences between the therapy groups were found. Conclusion: The findings presented in this study suggest a superiority of TMMR in comparison to the previously employed radical hysterectomy according to Wertheim-Meigs with regard to the postoperative quality of life, especially in the fields of physical activity and fatigue. This needs to be validated in the course of prospective, multicentre studies. In addition, it must be clarified as to what extent the found effects are, in particular, due to the omission of an additional radiotherapy.
Keywords: cervical cancer; cervix; gynaecology